Implementasi Model Pembelajaran Flipped Classroom dalam Pembelajaran Jarak Jauh untuk Meningkatkan Partisipasi Belajar IPA - Siti Nurkhasanah (Universitas Pendidikan Mandalika, 2021)
This study aims to describe the implementation of the flipped classroom learning model in distance learning to increase participation in science learning at SMP Negeri 1 Gangga. This research method used descriptive qualitative research. The subjects in this study were class IX.2 as many as 28 people. This research data collection technique used observation sheets, documentation, and tests. While the data analysis technique used qualitative and quantitative descriptive analysis. The results of this study indicate an increase in student participation in taking part in distance learning using the Flipped Classroom model, namely 10 people in week 1, 15 weeks 2, 22 weeks 3 and 24 people in week 4, while 4 other people join the study. outside the network. Furthermore, with regard to student responses, it shows that before the implementation of distance learning using the Flipped Classroom learning model as many as 50% of students are not happy, as many as 31% of students are not happy, and 17% of students are quite happy with distance learning. However, after using the Flipped Classroom learning model, 25% of students were unhappy, 25% of students were less than happy, 35% of students were happy, and 14% were very happy with distance learning.